Bridges between worlds: spirits and spirit work in Northern Iceland - Dempsey, Corinne G. ca. 20./21.Jh. (Oxford University Press, 2018)
Keeping track: a glossary of characters -- Bridging worlds with Andleg Mál -- Roots and layers of Andleg Mál -- Science and skepticism, belief and blasphemy -- Skyggnigáfa: the gift that keeps on giving -- Trance work -- Healers and healing -- Leaps of geography and faith